Analysis of the Factors Influencing Parents' Satisfaction with the Free School Lunch Program - Agrienta Bellanov; Lilis Nurhayati (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2026)
This study aims to analyze parents' responses to the trial implementation of the Free Nutritious Meal Program (MBG) conducted in several elementary schools in Trenggalek Regency. The MBG program, initiated by the government, is in its pilot stage and primarily targets improvements in students' nutritional intake, health, academic performance, and efforts to reduce stunting. mploying a mixed-methods approach, the research combined qualitative insights from in-depth interviews with parents, teachers, and school principals, alongside quantitative data gathered from structured questionnaires distributed to parents involved in the pilot program. The study evaluated variables such as food quality, hygiene, serving frequency, school–parent communication, and parental expectations and concerns regarding the program’s continuity. The findings reveal a largely positive response; parents particularly appreciated the program's role in fostering healthier eating habits and alleviating household financial burdens. However, several critical issues emerged, including limited menu variety, inconsistent food taste quality, and lack of transparency regarding meal schedules and nutritional content. Some parents expressed hope for the program’s expansion, provided that food quality and safety standards are maintained. Further analysis indicates that effective communication and parental involvement significantly influence satisfaction and support levels for the program. These insights offer valuable input for local governments and schools in refining MBG implementation to maximize its impact. This research contributes to a better understanding of the dynamics of the MBG pilot at the elementary school level and provides data-driven recommendations to enhance future policy and execution of free nutritious meal programs.